Polyacrylic acid powder binder, preparation method thereof, negative pole piece and battery

By preparing a high-viscosity polyacrylic acid powder binder and optimizing the viscosity of its aqueous solution and the solid content ratio of the negative electrode slurry, the problem of weak suspension and thickening ability of the existing polyacrylic acid binder was solved, the internal resistance of the battery was reduced and the cycle performance was improved, while the transportation cost was reduced.

CN120758201APending Publication Date: 2025-10-10WANHUA CHEM GRP BATTERY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510904269.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Most existing polyacrylic acid binders are in the form of aqueous solutions, resulting in high viscosity and weak suspension and thickening ability, which limits the increase in molecular weight. They need to be used with CMC, which leads to high battery internal resistance, reduced cycle performance, and high transportation costs.

Method used

Develop a polyacrylic acid powder binder. By controlling the viscosity of its aqueous solution and the solid content ratio of the negative electrode slurry, optimizing the weight-average molecular weight and particle size, and reducing the swelling degree, a high-viscosity powder binder is prepared using a simple preparation method.

Benefits of technology

The suspension thickening ability and processing efficiency of the binder are improved, the internal resistance of the battery is reduced, the battery cycle performance is improved and the transportation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a polyacrylic acid powder binder, a preparation method thereof, a negative pole piece and a battery. The polyacrylic acid powder binder comprises 0.95 wt%-1.05 wt% of an aqueous solution of the polyacrylic acid powder binder, wherein the viscosity of the aqueous solution is 1000 mPa.S to 4000 mPa.S; comprising the polyacrylic acid powder binder meets the following conditions: the standing time of the negative electrode paste is less than or equal to 7 days, and the ratio of the solid content of the upper-layer negative electrode paste to the solid content of the lower-layer negative electrode paste is (0.988-1.0): 1. According to the polyacrylic acid powder binder provided by the invention, the viscosity and the suspension thickening capability of the polyacrylic acid powder binder can be improved by limiting the viscosity of the aqueous solution of the polyacrylic acid powder binder and the ratio of the solid content of the upper layer to the solid content of the lower layer in the negative electrode slurry formed by the polyacrylic acid powder binder; when applied to the battery, the composite material can reduce the internal resistance of the battery and improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a polyacrylic acid powder binder and a preparation method thereof, a negative electrode sheet and a battery. Background Art

[0002] With the rapid development of lithium-ion batteries, binders, as a crucial component of batteries, have a crucial impact on battery performance. The binder's primary function is to firmly adhere the active material and conductive agent to the current collector, ensuring the structural stability of the electrode material during charge and discharge, preventing the active material from falling off and expanding, and thus maintaining the overall performance and life of the battery.

[0003] Currently, the most widely used negative electrode binders are sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). Hydrophilic CMC is insoluble in the electrolyte and does not swell, effectively maintaining a stable electrode structure. However, CMC itself has high impedance and is extremely hard and brittle after drying. Therefore, CMC is often used in combination with flexible SBR to improve the dispersibility of the SBR binder system.

[0004] In recent years, polyacrylic acid (PAA) binders, as a new type of water-based binder, have attracted attention due to their excellent adhesion and electrolyte resistance. The molecular structure of PAA contains rich functional groups that can form strong hydrogen bonds with the surface of the active material. Compared with the CMC+SBR combination, it can significantly improve the adhesion performance and cycle life of the electrode. However, the existing PAA binders in the industry are mostly supplied in the form of aqueous solutions. The extremely long molecular chain of PAA itself gives its aqueous solution a high viscosity. In order to ensure processing efficiency, the solid content of such products is generally limited to a low level, and the corresponding transportation costs are also high. At the same time, the limitation of the product's viscosity also makes it difficult to further increase the molecular weight of the PAA binder. Therefore, its suspension and thickening ability for the negative electrode active material is weak, and it is usually used in combination with CMC. The presence of CMC will lead to an increase in the internal resistance of the battery and a decrease in cycle performance. Summary of the Invention

[0005] The main purpose of the present invention is to provide a polyacrylic acid powder binder, which has a high aqueous solution viscosity and good suspension thickening ability, can reduce the internal resistance of the battery, improve the cycle performance of the battery, and reduce transportation costs.

[0006] The present invention also provides a method for preparing a polyacrylic acid powder binder, which can prepare the above-mentioned powder binder, has a simple process and low cost.

[0007] The present invention also provides a negative electrode plate, comprising the above-mentioned polyacrylic acid powder binder, which is applied to a battery to reduce the internal resistance of the battery and improve the cycle performance of the battery.

[0008] The present invention also provides a battery comprising the above-mentioned negative electrode plate, so that the battery has low internal resistance and excellent cycle performance.

[0009] In a first aspect, the present invention provides a polyacrylic acid powder binder, comprising 0.95wt%-1.05wt% of the polyacrylic acid powder binder, wherein the viscosity of the aqueous solution is 1000mPa·S-4000mPa·S;

[0010] The negative electrode slurry including the polyacrylic acid powder binder satisfies the following requirements: the negative electrode slurry is allowed to stand for ≤7 days, and the ratio of the solid content of the upper layer of the negative electrode slurry to the solid content of the lower layer of the negative electrode slurry is (0.988-1.0):1.

[0011] The polyacrylic acid powder binder as described above has a swelling degree of ≤1% in the electrolyte, wherein the electrolyte comprises a lithium salt and at least two of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.

[0012] The polyacrylic acid powder binder as described above, wherein the weight average molecular weight of the polyacrylic acid powder binder is 800,000-4,000,000;

[0013] And / or, the particle size D of the polyacrylic acid powder binder 50 1μm-90μm;

[0014] And / or, the moisture content of the polyacrylic acid powder binder is less than or equal to 5%.

[0015] In a second aspect, the present invention provides a method for preparing the polyacrylic acid powder binder as described above, comprising the following steps:

[0016] 1) performing a polymerization reaction on a raw material system comprising a polymerizable monomer and a functional monomer to obtain a polymer dispersion; wherein the functional monomer is used to improve the stability of the polymer dispersion;

[0017] 2) adding an organic solvent to the polymer dispersion to obtain a mixed solution;

[0018] 3) neutralizing the mixed solution and drying it to obtain the polyacrylic acid powder binder.

[0019] The preparation method of the polyacrylic acid powder binder as described above, wherein the functional monomer includes at least one of sodium allyl sulfonate, sodium α-olefin sulfonate, sodium p-styrene sulfonate, 2-acrylamido-2-methylpropane sulfonic acid, allyloxy nonylphenoxy propanol polyoxyethylene ether, and allyloxy nonylphenoxy propanol polyoxyethylene ether ammonium sulfate; preferably sodium allyl sulfonate and / or sodium p-styrene sulfonate;

[0020] And / or, the organic solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, butanone, acetonitrile, and tetrahydrofuran.

[0021] In the preparation method of the polyacrylic acid powder binder as described above, the mass percentage of the functional monomer in the raw material system is 0.1%-3%;

[0022] And / or, the mass ratio of the organic solvent to the polymer dispersion is (1-5):1, preferably (1.5-4):1.

[0023] In the preparation method of the polyacrylic acid powder binder as described above, the polymerizable monomers include unsaturated carboxylic acid monomers, unsaturated nitrile monomers and unsaturated amide monomers; and the following conditions are met:

[0024] The mass percentage of the unsaturated carboxylic acid monomer in the raw material system is 30%-50%;

[0025] And / or, the mass percentage of the unsaturated nitrile monomer in the raw material system is 40%-60%;

[0026] And / or, the mass percentage of the unsaturated amide monomer in the raw material system is 3%-13%;

[0027] and / or, the unsaturated carboxylic acid monomer comprises at least one of acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid, preferably acrylic acid and / or methacrylic acid;

[0028] and / or, the unsaturated nitrile monomer comprises at least one of acrylonitrile, α-haloacrylonitrile, and α-alkylacrylonitrile, preferably acrylonitrile;

[0029] And / or, the unsaturated amide monomer includes at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-vinyl formamide, N-acryloylmorpholine, and N-acryloyl pyrrolidone, preferably acrylamide.

[0030] The preparation method of the polyacrylic acid powder binder as described above, wherein the raw material system further includes a protective glue and an initiator;

[0031] The protective glue includes at least one of polyvinyl alcohol, polyvinyl pyrrolidone, and sodium carboxymethyl cellulose;

[0032] And / or, the initiator includes at least one of ammonium sulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, hydrogen peroxide, isoascorbic acid, sodium metabisulfite and sodium bisulfite.

[0033] In a third aspect, the present invention provides a negative electrode plate, comprising the polyacrylic acid powder binder as described above or a polyacrylic acid powder binder prepared according to the preparation method of the polyacrylic acid powder binder as described above.

[0034] In a fourth aspect, the present invention provides a battery comprising the negative electrode plate as described above.

[0035] The polyacrylic acid powder binder provided by the present invention can improve the viscosity of the aqueous solution containing the polyacrylic acid powder binder and the ratio of the upper solid content to the lower solid content in the negative electrode slurry formed by the powder binder, thereby improving the viscosity of the powder binder and the suspension thickening ability of the slurry. The good suspension thickening ability ensures the uniform distribution of the negative electrode active material and conductive agent in the electrode, reduces obstacles in the current conduction path, and when applied to batteries, can reduce the battery's internal resistance and improve the battery's cycle performance. In addition, the powder binder can also reduce transportation costs. DETAILED DESCRIPTION

[0036] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0037] Thanks to my country's policy support for new energy, the power, energy storage, and traditional consumer electronics sectors are developing rapidly, and correspondingly, the requirements for lithium-ion battery performance are becoming increasingly stringent, such as long cycle life, high energy density, high rate capability, and high safety. Lithium-ion batteries are primarily composed of a positive electrode, a negative electrode, an electrolyte, a separator, and various auxiliary materials (conductive agents, binders). Among them, the binder, while accounting for a relatively low proportion of the battery cost, plays a key role. It adheres the active material and conductive agent to the current collector, ensuring overall connectivity between them. It also effectively limits the volume expansion and shedding of the active material during charge and discharge, maintaining the structural integrity of the battery during use.

[0038] Currently, the most widely used negative electrode binders are sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber latex (SBR). The hydrophilic CMC is insoluble in the electrolyte and does not swell, effectively maintaining adhesion and electrode structural stability. However, CMC itself has high impedance and is extremely brittle after drying. Therefore, it is often mixed with SBR to improve SBR's high swelling and poor dispersibility, leveraging its suspension-thickening properties. Conversely, SBR's high flexibility and low internal resistance can offset CMC's shortcomings. Mixing the two can combine and offset each other's strengths and weaknesses, resulting in a negative electrode sheet with excellent adhesion and flexibility. PAA-based binders are a new type of water-based binder. Their side chains contain abundant functional groups that can form hydrogen bonds with the negative electrode active material, exhibiting far superior adhesion compared to the CMC+SBR combination. They also possess high tensile strength and excellent electrolyte resistance, resulting in lithium batteries with superior cycle life and capacity retention compared to the CMC+SBR combination.

[0039] However, existing PAA binders are mostly in aqueous solution form. The polymer's extremely long molecular chains impart high viscosity to these solutions, resulting in generally low solids content and high transportation costs. Furthermore, the high viscosity of PAA aqueous solutions limits further increases in molecular weight, limiting their efficiency. Consequently, their ability to suspend and thicken negative electrode active materials is weaker than that of CMC, requiring their use in combination with CMC. However, this combination can result in higher internal resistance in batteries and reduced cycle performance.

[0040] The inventors of the present application have discovered that developing a PAA powder binder with higher viscosity and better suspension and thickening ability can reduce the internal resistance of the battery, improve the cycle performance of the battery, and reduce transportation costs.

[0041] Based on this, in the first aspect, the present invention provides a polyacrylic acid powder binder, comprising an aqueous solution containing 0.95wt%-1.05wt% of the polyacrylic acid powder binder, the viscosity of which is 1000mPa·S-4000mPa·S, for example, it can be 1000mPa·S, 1500mPa·S, 2000mPa·S, 3000mPa·S, 4000mPa·S or a range consisting of any two thereof; the negative electrode slurry comprising the polyacrylic acid powder binder satisfies: the negative electrode slurry standing time is ≤7 days, and the ratio of the solid content of the upper negative electrode slurry to the solid content of the lower negative electrode slurry is (0.988-1.0):1, for example, it can be 0.988:1, 0.990:1, 0.992:1, 0.995:1, 0.997:1, 0.999:1, 1.0:1 or a range consisting of any two thereof.

[0042] Illustratively, the mass percentage of the polyacrylic acid powder binder in the aqueous solution can be 0.95 wt%, 0.97 wt%, 0.99 wt%, 1 wt%, 1.02 wt%, 1.05 wt% or a range consisting of any two thereof.

[0043] The polyacrylic acid powder binder provided by the present invention can improve the viscosity and suspension thickening ability of the polyacrylic acid powder binder by limiting the viscosity of the aqueous solution containing the polyacrylic acid powder binder and the ratio of the upper solid content to the lower solid content in the negative electrode slurry formed by the polyacrylic acid powder binder. When applied to batteries, it can reduce the internal resistance of the battery and improve the battery's cycle performance. The reason for this is that the viscosity of the polyacrylic acid powder binder in aqueous solution ensures that the binder has sufficient fluidity when forming the electrode slurry, facilitating processing and coating, while also providing sufficient adhesion to maintain the stable bonding of the active material and the conductive agent. In addition, the moderate viscosity facilitates the formation of a uniform electrode coating, reducing defects and unevenness in the coating, thereby reducing the internal resistance of the battery. The ratio of the solid content of the upper negative electrode slurry to the solid content of the lower negative electrode slurry reflects the suspension stability of the binder. An appropriate ratio indicates that the negative electrode slurry will not undergo significant sedimentation and stratification during standing, indicating that the binder has good dispersibility and suspension stability for the negative electrode active material. Good suspension stability ensures uniform distribution of the negative electrode active material and conductive agent within the electrode, reducing obstructions in the current conduction path and thereby lowering the battery's internal resistance. Furthermore, good suspension stability prevents flocculation and sedimentation of the negative electrode slurry during processing and coating, ensuring uniform coating of the electrode sheet and reducing defects. Furthermore, the uniform distribution of the negative electrode active material and conductive agent also helps improve the mechanical strength and durability of the electrode, thereby enhancing the battery's cycling performance.

[0044] Therefore, the polyacrylic acid powder binder provided by the present invention can improve the viscosity and suspension thickening ability of the polyacrylic acid powder binder by limiting the viscosity of the aqueous solution of the polyacrylic acid powder binder and the ratio of the upper solid content to the lower solid content in the negative electrode slurry formed by the polyacrylic acid powder binder. When applied to a battery, it can reduce the internal resistance of the battery and improve the cycle performance of the battery.

[0045] In addition, the polyacrylic acid binder of the present invention is in powder form, which can greatly reduce the transportation cost of the binder and improve the processing and use efficiency compared to the traditional high-viscosity aqueous solution form of PAA.

[0046] In the present invention, when testing the viscosity of the polyacrylic acid powder binder, the polyacrylic acid powder binder can be dissolved in water at 24° C. to form a solution at a mass fraction of 0.95% to 1.05%, and then the viscosity of the solution is tested using a Brookfield DV2T viscosity tester.

[0047] The polyacrylic acid powder binder dissolves in water for no more than 3 hours, and the pH value of the resulting solution is 7-9.

[0048] To test the stability of the negative electrode slurry, the prepared negative electrode slurry (for example, 1.5 parts of a polyacrylic acid powder binder, 2 parts of carbon black as a conductive agent, and 96.5 parts of graphite as the negative electrode active material) can be added to 100 parts of water, stirred at high speed for 30 minutes to mix evenly, and filtered through a 100-mesh filter to obtain the negative electrode slurry) and left to stand at room temperature for 2 days. The stratification of the negative electrode slurry can be observed, and the solid content of the upper and lower layers of the negative electrode slurry can be measured to determine the stability of the negative electrode slurry. The upper layer and lower layer refer to the upper and lower surfaces of the container containing the negative electrode slurry, respectively.

[0049] In some embodiments of the present invention, the swelling degree of the polyacrylic acid powder binder in the electrolyte is ≤ 1%, for example, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, or any two thereof. The electrolyte includes a lithium salt and at least two of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and diethyl carbonate (DEC). For example, the volume ratio of EC:EMC:DEC is 3:5:2, and the volume ratio of EC:DEC:PC:EP is 3:3:1:3.

[0050] The swelling degree of the polyacrylic acid powder binder in the electrolyte reflects the absorption and expansion behavior of the binder in the electrolyte. The swelling degree of the polyacrylic acid powder binder in the electrolyte of the present invention is within the above range. Its slight swelling can ensure that the electrolyte can penetrate into the interior of the electrode and ensure the ion conductivity. At the same time, the binder can also have a certain degree of flexibility and elasticity, which helps to buffer the stress caused by the volume change of the electrode material during the charge and discharge process, thereby improving the structural stability and cycle life of the electrode. In addition, the low swelling characteristics of the binder can reduce the particle gaps of the negative electrode active material, ensuring that the conductivity between the negative electrode active material and the current collector will not cause the collapse and failure of the electrode structure and the increase of the thickness of the electrode sheet due to excessive swelling, thereby improving the electrochemical performance of the battery.

[0051] In the present invention, when testing the swelling degree of the polyacrylic acid powder binder in the electrolyte, the polyacrylic acid powder binder can be dissolved in water at 24°C-26°C at a mass fraction of 0.95%-1.05% to form a solution, and then the solution is dried to form a film to test the swelling degree of the polyacrylic acid powder binder in the electrolyte.

[0052] Specifically, the solution can be dried in an oven at 49°C-51°C to form a membrane. A membrane sheet with a mass of M1 is taken. The membrane sheet is then immersed in an electrolyte solution (EC, EMC, and DEC in a volume ratio of 3:5:2) and placed in an oven at 59°C-61°C for 45-50 hours. The electrolyte on the membrane surface is wiped dry with filter paper and weighed, recording it as M2. The swelling degree is calculated using the following formula: Swelling degree = (M2 - M1) / M1 × 100%.

[0053] In some embodiments of the present invention, the weight average molecular weight of the polyacrylic acid powder binder is 800,000-4,000,000, for example, 800,000, 1,000,000, 2,000,000, 3,000,000, 4,000,000 or any two thereof.

[0054] The right weight-average molecular weight range ensures that the adhesive provides sufficient adhesion while maintaining good processing properties. By optimizing the molecular weight, a balance can be achieved between adhesion and processing properties.

[0055] In the present invention, the weight average molecular weight of the polyacrylic acid powder binder can be tested by gel permeation chromatography (GPC), and the buffer solution is a sodium chloride / sodium dihydrogen phosphate system.

[0056] In some embodiments, the particle size D of the polyacrylic acid powder binder is 50 The particle size is 1 μm to 90 μm, for example, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or any combination thereof, which can provide good dispersion and uniformity during electrode preparation. It is also beneficial to reduce sedimentation and stratification of the slurry and improve the stability of the slurry.

[0057] In the present invention, the particle size D of the polyacrylic acid powder binder is 50 It can be obtained by testing with a laser particle size analyzer.

[0058] In some embodiments, the moisture content of the polyacrylic acid powder binder is less than or equal to 5%, for example, 0.1%, 1%, 2%, 3%, 4%, 5%, or any two thereof, which helps improve the storage stability and transportation efficiency of the polyacrylic acid powder binder. A lower moisture content reduces the risk of moisture absorption and agglomeration of the polyacrylic acid powder binder during storage, ensuring its fluidity and dispersibility during use. In addition, the low moisture content of the powder form reduces unnecessary weight and volume during transportation, thereby reducing transportation costs.

[0059] In the present invention, the moisture content of the polyacrylic acid powder binder can be measured by a high-precision solid content tester QL-720D.

[0060] In a second aspect, the present invention provides a method for preparing the polyacrylic acid powder binder as described above, comprising the following steps:

[0061] 1) performing a polymerization reaction on a raw material system including a polymerizable monomer and a functional monomer to obtain a polymer dispersion; wherein the functional monomer is used to improve the stability of the polymer dispersion;

[0062] 2) adding an organic solvent to the polymer dispersion to obtain a mixed solution;

[0063] 3) The mixed liquid is neutralized and dried to obtain a polyacrylic acid powder binder.

[0064] In the present invention, in step 1), a functional monomer is added to the raw material system to carry out a polymerization reaction. The addition of the functional monomer can improve the stability of the polymer formed by the polymerization reaction and prevent the polymer from agglomerating, which leads to incomplete subsequent neutralization treatment and thus affects the performance of the final binder.

[0065] In step 2), the addition of the organic solvent can reduce the solubility of the final binder polymer in the mixed solvent, so that the polymer can be condensed and precipitated from the mixed solvent after the neutralization process is completed, and a powdered binder is obtained after drying.

[0066] In step 3), the mixed solution is neutralized. This reduces the solubility of the binder in the organic phase, allowing it to precipitate from the mixed solution. It also provides charge repulsion for the precipitated polymer particles, preventing them from settling and sticking, thereby obtaining a polyacrylic acid powder binder. The neutralizing agent can be selected from at least one of aqueous solutions of Na2CO3, K2CO3, Li2CO3, NaOH, KOH, and LiOH. After the polymer undergoes a phase transition from swelling to dissolution to coagulation, the neutralization treatment is completed, resulting in a binder with a neutral pH. The addition of functional monomers can promote the polymer coagulation process.

[0067] In addition, in step 1), a polymer dispersion can be prepared by aqueous precipitation polymerization to ensure that the polymer has a large molecular weight, thereby providing a guarantee for the adhesion performance of the binder and also playing a role in suspending and thickening the active substance.

[0068] The polymerization reaction temperature is 35°C-80°C, for example, 35°C, 40°C, 50°C, 60°C, 70°C, 80°C or any two thereof.

[0069] In step 3), with the dropwise addition of the neutralizing agent, the time from the beginning of swelling to the dissolution of the polymer is 0.5h-5h, preferably 1.5-3h; the polymer coagulation process occurs when its pH is in the range of 6-9, preferably 7-8, and the particle size after coagulation is 50μm-1000μm.

[0070] Neutralization can be performed at low to medium temperatures, significantly reducing energy consumption and improving production efficiency. The neutralization temperature is 25-50°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, or any combination thereof.

[0071] After neutralization, the polymer can be dried by spray drying, which can quickly remove water and organic solvents from the polymer with high drying efficiency. The spray drying temperature is 110-150°C, for example, 110°C, 120°C, 130°C, 140°C, 150°C, or any combination thereof.

[0072] The preparation method of the polyacrylic acid powder binder provided by the present invention can prepare the above-mentioned polyacrylic acid powder binder, and the polyacrylic acid powder binder has high viscosity and good suspension and thickening ability, which can reduce the internal resistance of the battery and improve the cycle performance of the battery.

[0073] In some embodiments of the present invention, the functional monomer includes at least one of sodium allyl sulfonate, sodium α-olefin sulfonate, sodium p-styrene sulfonate, 2-acrylamido-2-methylpropane sulfonic acid, allyloxy nonylphenoxy propanol polyoxyethylene ether, and allyloxy nonylphenoxy propanol polyoxyethylene ether ammonium sulfate; preferably sodium allyl sulfonate and / or sodium p-styrene sulfonate.

[0074] The above functional monomers can further improve the stability of the polymer dispersion.

[0075] In some embodiments, the organic solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, butanone, acetonitrile, and tetrahydrofuran.

[0076] In the present application, the organic solvent is a low-boiling organic solvent that is miscible with water, including lower alcohols with lower boiling points such as methanol, ethanol, n-propanol, isopropanol, tert-butanol, and the like, and ketones such as acetone, butanone, acetonitrile, tetrahydrofuran, and the like.

[0077] The above-mentioned organic solvent can significantly reduce the solubility of the final neutral binder in the mixed solvent, which is beneficial to the precipitation of the binder, and finally a powder binder is obtained after drying. Moreover, the above-mentioned organic solvent has a lower boiling point and is easy to be distilled and recovered from water, and can be recycled for subsequent use.

[0078] In some embodiments of the present application, the functional monomer accounts for 0.1%-3% of the mass percentage of the raw material system, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or a range consisting of any two of them.

[0079] In some embodiments, the mass ratio of the organic solvent to the polymer dispersion is (1-5):1, for example, it can be 1:1, 1.5:1, 2:1, 3:1, 4:1, 5:1, or a range consisting of any two of them, preferably (1.5-4):1. It can not only effectively reduce the solubility of the final binder, but also reduce the consumption of the organic solvent, thereby reducing the production cost and environmental impact.

[0080] In some embodiments of the present application, the polymerizable monomer includes unsaturated carboxylic acid monomer, unsaturated nitrile monomer, and unsaturated amide monomer; and satisfies:

[0081] The unsaturated carboxylic acid monomer accounts for 30%-50% of the mass percentage of the raw material system, for example, it can be 30%, 35%, 40%, 45%, 50%, or a range consisting of any two of them.

[0082] In some embodiments, the unsaturated nitrile monomer accounts for 40%-60% of the mass percentage of the raw material system, for example, it can be 40%, 45%, 50%, 55%, 60%, or a range consisting of any two of them.

[0083] In some embodiments, the unsaturated amide monomer accounts for 3%-13% of the mass percentage of the raw material system, for example, it can be 3%, 5%, 7%, 9%, 11%, 13%, or a range consisting of any two of them.

[0084] In some embodiments, the unsaturated carboxylic acid monomer includes at least one of acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, preferably acrylic acid and / or methacrylic acid.

[0085] In some embodiments, the unsaturated nitrile monomer includes at least one of acrylonitrile, alpha-haloacrylonitrile, alpha-alkylacrylonitrile, preferably acrylonitrile. In some embodiments, the unsaturated amide monomer includes at least one of acrylamide, methacrylamide, maleic acid amide, and the like, preferably acrylamide.

[0086] In some embodiments, the unsaturated amide monomer includes at least one of acrylamide, methacrylamide, N-methylol acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-vinyl formamide, N-acryloylmorpholine, and N-acryloyl pyrrolidone, preferably acrylamide.

[0087] The types and contents of the above-mentioned polymerizable monomers can effectively polymerize to form a polyacrylic acid (PAA) binder, and the binder has high viscosity and good suspension stability, which can reduce the internal resistance of the battery and improve the cycle performance of the battery.

[0088] In some embodiments of the present invention, the raw material system further includes a protective colloid and an initiator.

[0089] The protective colloid includes at least one of polyvinyl alcohol, polyvinyl pyrrolidone and sodium carboxymethyl cellulose.

[0090] In some embodiments, the mass percentage of the protective glue in the raw material system is 0.5%-2%, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 2% or any two thereof.

[0091] In the present invention, the type and content of the protective colloid can provide a stable reaction environment during the polymerization process, preventing aggregation and sedimentation of polymer particles, thereby improving the stability of the dispersion. It can also regulate the viscosity and rheology of the system, helping to control the morphology and size of the polymer, ensuring the uniformity and consistency of the final product. Furthermore, the presence of the protective colloid can enhance the mechanical properties of the polymer, such as toughness and tensile strength, and improve the adhesion of the binder to the electrode material.

[0092] In some embodiments, the initiator includes at least one of ammonium sulfate, sodium persulfate, potassium persulfate, t-butyl hydroperoxide, hydrogen peroxide, isoascorbic acid, sodium metabisulfite, and sodium bisulfite.

[0093] The above-mentioned initiator can effectively initiate free radical polymerization reaction and ensure the efficient progress of the polymerization process.

[0094] In a third aspect, the present invention provides a negative electrode plate, comprising the powder binder as described above or a powder binder prepared according to the preparation method of the powder binder as described above, which can be applied to a battery to reduce the internal resistance of the battery and improve the cycle performance of the battery.

[0095] The negative electrode sheet of the present invention further comprises a negative electrode active material and a conductive agent. The negative electrode active material can be a conventional negative electrode active material in the art, such as artificial graphite, natural graphite, hard carbon, silicon carbon, etc.

[0096] In a fourth aspect, the present invention provides a battery comprising the negative electrode plate as described above. The battery has advantages corresponding to the above-mentioned negative electrode plate, which will not be described in detail.

[0097] The battery of the present invention includes, in addition to the negative electrode sheet, a positive electrode sheet, a separator, and an electrolyte. The electrolyte can refer to conventional electrolytes in the art, and the separator can also be a separator commonly used in the art, such as PP film, PE film, etc.

[0098] The battery of the present invention can be prepared by conventional methods in the field. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and then the battery cell can be obtained through a lamination or winding process, and then through baking, liquid injection, formation, packaging and other processes to obtain the above-mentioned battery.

[0099] The present application is further described in detail below with reference to specific examples. These examples are not to be construed as limiting the scope of protection claimed in this application. Unless otherwise specified, the chemical reagents used in each example and comparative example are commercially available and are of analytical grade. The main raw materials are as follows:

[0100] Acrylic acid (AA), manufacturer: Wanhua Chemical;

[0101] Methacrylic acid (MAA), manufacturer: Wanhua Chemical;

[0102] Acrylamide (AM), manufacturer: Wanhua Chemical;

[0103] Acrylonitrile (AN), manufacturer: Wanhua Chemical;

[0104] Sodium p-styrene sulfonate (SSS), manufacturer: Myrel;

[0105] Ammonium persulfate (APS), manufacturer: Jinan Jinhao Chemical Co., Ltd.

[0106] Sodium metabisulfite (Na2S2O5), manufacturer: Wanhua Chemical;

[0107] Sodium carboxymethyl cellulose (CMC), manufacturer: Sinopec Sichuan Wei Co., Ltd.

[0108] Polyvinyl alcohol (PVA), manufacturer: Sinopharm Chemical;

[0109] Sodium carboxymethyl cellulose (CMC), manufacturer: Sinopharm Chemical;

[0110] Sodium hydroxide (NaOH), manufacturer: Inokane;

[0111] Conductive carbon black (Super-P), manufacturer: Yiruishi Group;

[0112] Graphite (G), manufacturer: Shanshan Co., Ltd.

[0113] Example 1

[0114] The preparation method of the polyacrylic acid powder binder of this embodiment comprises the following steps:

[0115] 1) Add 3g CMC and 1500g deionized water into a reactor, start stirring under a nitrogen atmosphere and set the heating temperature to 70°C, stirring and dissolving to obtain a protective glue solution.

[0116] 2) Add 30g AM, 120g AA, 147g AN, and 3g SSS to the reactor in sequence and stir thoroughly.

[0117] 3) Prepare an APS aqueous solution (0.3g APS dissolved in 50g deionized water). After the reactor temperature reaches 60°C, continuously add the APS aqueous solution dropwise to the reactor over 5 hours to form a raw material system. Maintain the temperature for 1 hour to allow polymerization to proceed. After the reaction, cool the mixture to obtain a polymer dispersion. AM accounts for 10.0% of the total weight of the polymerized monomers and functional monomers, AA accounts for 40%, AN accounts for 49%, and SSS accounts for 1%.

[0118] 4) Add tert-butanol to the polymer dispersion, stir thoroughly, and then raise the temperature in the autoclave to 35° C. to obtain a mixed solution, wherein the mass ratio of the organic solvent tert-butanol to the dispersion is 3:1.

[0119] 5) Sodium hydroxide aqueous solution (15%) was continuously added dropwise to the mixed solution to neutralize it to pH = 7.5 to obtain a neutral polymer particle suspension.

[0120] 6) The neutral polymer particle suspension was spray-dried using a spray dryer (drying temperature: 130° C.) to obtain a polyacrylic acid powder binder.

[0121] Example 2

[0122] The preparation method of the polyacrylic acid powder binder in Example 2 is basically the same as that in Example 1, except that the configuration of the APS aqueous solution in step 3) is as follows: 0.9 g APS is dissolved in 50 g deionized water, and after the temperature in the reactor rises to 70°C, the APS aqueous solution is continuously added dropwise to the reactor, and the addition is completed within 5 hours.

[0123] Example 3

[0124] The preparation method of the polyacrylic acid powder binder in Example 3 is basically the same as that in Example 1, except that the configuration of the APS aqueous solution in step 3) is as follows: 0.12 g APS is dissolved in 50 g deionized water, and after the temperature in the reactor rises to 70°C, the APS aqueous solution is continuously added dropwise to the reactor, and the addition is completed within 5 hours.

[0125] Example 4

[0126] The preparation method of the polyacrylic acid powder binder of Example 4 is basically the same as that of Example 1, except that, in step 3), an oxidation-reduction initiator is prepared, 0.6 g of APS is dissolved in 50 g of deionized water to obtain an oxidant solution, and 0.3 g of Na2S2O5 is dissolved in 50 g of deionized water to obtain a reducing agent solution; the polymerization temperature is 40°C.

[0127] Example 5

[0128] The preparation method for the polyacrylic acid powder binder in Example 5 is essentially the same as that in Example 1, except that in step 2), 30g AM, 120g AA, 149.7g AN, and 0.3g SSS are sequentially added to the reaction kettle and thoroughly stirred. AM accounts for 10% of the total mass of the polymerized monomers and functional monomers, AA accounts for 40% of the total mass of the polymerized monomers and functional monomers, AN accounts for 49.9% of the total mass of the polymerized monomers and functional monomers, and SSS accounts for 0.1% of the total mass of the polymerized monomers and functional monomers.

[0129] Example 6

[0130] The preparation method for the polyacrylic acid powder binder of Example 6 is essentially the same as that of Example 1, except that in step 2), 30g AM, 120g AA, 141g AN, and 9g SSS are sequentially added to the reaction kettle and thoroughly stirred. AM accounts for 10% of the total mass of the polymerized monomers and functional monomers, AA accounts for 40% of the total mass of the polymerized monomers and functional monomers, AN accounts for 47% of the total mass of the polymerized monomers and functional monomers, and SSS accounts for 3% of the total mass of the polymerized monomers and functional monomers.

[0131] Example 7

[0132] The preparation method of the polyacrylic acid powder binder of Example 7 is basically the same as that of Example 1, except that, in step 4), the mass ratio of the organic solvent tert-butanol to the dispersion is 1.5:1.

[0133] Example 8

[0134] The preparation method of the polyacrylic acid powder binder of Example 8 is basically the same as that of Example 1, except that, in step 4), the mass ratio of the organic solvent tert-butanol to the dispersion is 4:1.

[0135] Comparative Example 1

[0136] The preparation methods of the binders of Comparative Example 1 and Example 1 are basically the same, except that the functional monomer SSS is not added in step 2).

[0137] Comparative Example 2

[0138] Comparative Example 2 was prepared using a method essentially identical to that of Example 1, except that step 4) was omitted, i.e., tert-butyl alcohol was not added to the dispersion. The polymer prepared in this comparative example completely dissolved during the neutralization process, resulting in a PAA solution. Spray drying to produce a powdered binder was not possible.

[0139] Comparative Example 3

[0140] The adhesive in Comparative Example 3 is commercially available LA136D solution-type PAA adhesive.

[0141] Comparative Example 4

[0142] The binder of Comparative Example 4 is a combination of commercially available LA136D solution-type PAA binder and CMC, with a mass ratio of 1.5:0.5.

[0143] Test example:

[0144] Preparation of lithium-ion battery anode: Add 1.5 parts binder, 2 parts conductive carbon black (SP), and 96.5 parts anode active material (graphite) to 100 parts water at room temperature. Stir at high speed for 30 minutes to mix thoroughly. Filter through a 100-mesh filter to obtain anode slurry. The anode slurry was then evaluated for slurry stability.

[0145] The negative electrode slurry was coated onto 10μm-thick copper foil to a thickness of 100μm. The slurry was then dried at 135°C for 25 minutes, naturally cooled to room temperature in an oven, and rolled on a roller press to produce the negative electrode sheet. The negative electrode sheet was then tested for peel strength and electrochemical performance.

[0146] 1. Binder viscosity evaluation method: The instrument used is a Brookfield DV2T tester. Specifically, the powdered binder is prepared into a 1wt% aqueous solution, which is placed under the instrument after being kept at a constant temperature of 25°C. A 64# rotor is selected and the test conditions are 12 rpm. The rotor groove is kept level with the liquid surface, and the test is started. The viscosity reading is read after it stabilizes. The test is repeated three times and the average value is taken.

[0147] 2. Swelling Degree Evaluation Method: After preparing a 1wt% aqueous solution of the binder, dry it to form a film. The swelling degree of the binder in the electrolyte is then tested. Specifically, the aqueous solution is dried in a 50°C oven to form a film. A film with a mass of M1 is taken. The film is then immersed in an electrolyte (EC, EMC, and DEC in a volume ratio of 3:5:2) and placed in a 60°C oven for 48 hours. The electrolyte on the membrane surface is then wiped clean with filter paper and weighed, recording the mass as M2. The swelling degree is calculated using the following formula: Swelling Degree = (M2 - M1) / M1 × 100%.

[0148] 3. Slurry stability evaluation method: The prepared negative electrode slurry is placed at room temperature for 2 days. The slurry is observed for stratification and the solid content of the upper and lower layers of the slurry is measured to determine the slurry stability. The upper and lower layers refer to the upper and lower surfaces of the slurry container, respectively.

[0149] 4. Weight average molecular weight test of the binder: The test was conducted by gel permeation chromatography (GPC), and the buffer solution used was a sodium chloride / sodium dihydrogen phosphate system.

[0150] 5. Particle size D of binder 50 : Tested using a laser particle size analyzer.

[0151] 6. Moisture content of binder: obtained by testing with high-precision solid content tester QL-720D.

[0152] 7. Peel Strength Evaluation Method: The instrument uses a Kejian tensile testing machine. Specifically, the electrode sheet prepared above is cut into electrode sheets with a length of 200 mm and a width of 25 mm along the rolling direction. The electrode sheet is flatly affixed to a smooth steel plate using 3M double-sided tape. The stainless steel plate is then fixed to the tensile testing machine. The electrode sheet not affixed to the tape is reversely clamped to the tensile testing machine probe. The tensile testing machine base pulls the electrode sheet at a speed of 10 cm / min. The sensor measures the peel force during this process. Five parallel samples are tested in each group, and the average value is the final peel strength, expressed in N / m.

[0153] 8. Electrochemical performance evaluation method: Prepare the positive electrode sheet using lithium iron phosphate as the positive electrode active material. The preparation method is the same as that of the negative electrode sheet. Assemble the negative and positive electrode sheets into an aluminum-plastic soft-package battery, and then test the electrochemical performance of the battery.

[0154] DCR: At 25°C and -10°C, the battery was discharged at a 1C constant current to 2.75V, allowed to rest, then charged at a 1C constant current to 4.2V and maintained at a constant voltage of 4.2V. The battery was then discharged at a 1C rate to 2.8V, and the capacity was recorded. After 2-4 cycles, the final discharge capacity was used as the 100% capacity value for subsequent DCR tests. At the target temperature, the battery was charged at a 1C rate to 4.2V and maintained at a constant voltage of 4.2V. The battery was then discharged at a 1C rate to 50% SOC and allowed to rest. The battery was discharged at 3C for 30s and then discharged at a 1C rate to 2.75V. The DCR value was calculated using the formula DCR = (U2 - U1) / I, where I is the discharge current, U1 is the sampled voltage at the end of the rest period and the start of discharge, and U2 is the voltage at the end of discharge.

[0155] Cycling performance: Using Land CT2001A, at 25°C, charge to 4.2V at a constant current of 1C, then charge to 4.2V at a constant voltage of 1C, and then discharge to 2.8V at a discharge rate of 1C. Repeat this charge and discharge cycle 1000 times. Measure the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 1000th cycle. 1000 The capacity retention rate after 1000 cycles is Q=Q 1000 / Q1×100%.

[0156] Table 1

[0157]

[0158] As shown in Table 1, compared with the comparative example, the polyacrylic acid powder binder provided by the present invention can improve the viscosity of the aqueous solution including the polyacrylic acid powder binder and the ratio of the upper solid content to the lower solid content in the negative electrode slurry formed by the powder binder, thereby improving the viscosity of the powder binder and the suspension thickening ability of the slurry. The good suspension thickening ability ensures the uniform distribution of the negative electrode active material and the conductive agent in the electrode, reduces the obstruction in the current conduction path, and when applied to the battery, can reduce the internal resistance of the battery and improve the battery cycle performance. In addition, the powder binder can also reduce transportation costs.

[0159] Finally, it should be noted that those skilled in the art will readily identify other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses, or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art not disclosed herein. The present invention is not limited to the foregoing description and may be modified and altered in various ways without departing from the scope thereof. The scope of the present invention is limited solely by the appended claims.

Claims

1. A polyacrylic acid powder binder, characterized in that: The viscosity of the aqueous solution comprising 0.95wt%-1.05wt% of the polyacrylic acid powder binder is 1000mPa·S-4000mPa·S; The negative electrode slurry including the polyacrylic acid powder binder satisfies the following requirements: the negative electrode slurry is allowed to stand for ≤7 days, and the ratio of the solid content of the upper layer of the negative electrode slurry to the solid content of the lower layer of the negative electrode slurry is (0.988-1.0):

1.

2. The polyacrylic acid powder binder according to claim 1, characterized in that: The swelling degree of the polyacrylic acid powder binder in the electrolyte is ≤1%, wherein the electrolyte includes lithium salt and at least two of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.

3. The polyacrylic acid powder binder according to claim 1 or 2, characterized in that: The weight average molecular weight of the polyacrylic acid powder binder is 800,000-4,000,000; And / or, the particle size D of the polyacrylic acid powder binder 50 1μm-90μm; And / or, the moisture content of the polyacrylic acid powder binder is less than or equal to 5%.

4. A method for preparing the polyacrylic acid powder binder according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) performing a polymerization reaction on a raw material system comprising a polymerizable monomer and a functional monomer to obtain a polymer dispersion; wherein the functional monomer is used to improve the stability of the polymer dispersion; 2) adding an organic solvent to the polymer dispersion to obtain a mixed solution; 3) neutralizing the mixed solution and drying it to obtain the polyacrylic acid powder binder.

5. The method for preparing the polyacrylic acid powder binder according to claim 4, wherein: The functional monomer includes at least one of sodium allyl sulfonate, sodium α-olefin sulfonate, sodium p-styrene sulfonate, 2-acrylamido-2-methylpropane sulfonic acid, allyloxy nonylphenoxy propanol polyoxyethylene ether, and allyloxy nonylphenoxy propanol polyoxyethylene ether ammonium sulfate; preferably sodium allyl sulfonate and / or sodium p-styrene sulfonate; And / or, the organic solvent includes at least one of methanol, ethanol, n-propanol, isopropanol, tert-butanol, acetone, butanone, acetonitrile, and tetrahydrofuran.

6. The method for preparing the polyacrylic acid powder binder according to claim 4 or 5, characterized in that: The percentage of the functional monomer to the total mass of the polymerized monomer and the functional monomer is 0.1%-3%; And / or, the mass ratio of the organic solvent to the polymer dispersion is (1-5):1, preferably (1.5-4):

1.

7. The method for preparing the polyacrylic acid powder binder according to any one of claims 4 to 6, characterized in that: The polymerizable monomers include unsaturated carboxylic acid monomers, unsaturated nitrile monomers and unsaturated amide monomers; and satisfy the following requirements: The unsaturated carboxylic acid monomer accounts for 30% to 50% of the total mass of the polymerizable monomer and the functional monomer; And / or, the unsaturated nitrile monomer accounts for 40% to 60% of the total mass of the polymerizable monomer and the functional monomer; And / or, the unsaturated amide monomer accounts for 3% to 13% of the total mass of the polymerizable monomer and the functional monomer; and / or, the unsaturated carboxylic acid monomer comprises at least one of acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid, preferably acrylic acid and / or methacrylic acid; and / or, the unsaturated nitrile monomer comprises at least one of acrylonitrile, α-haloacrylonitrile, and α-alkylacrylonitrile, preferably acrylonitrile; And / or, the unsaturated amide monomer includes at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-vinyl formamide, N-acryloylmorpholine, and N-acryloyl pyrrolidone, preferably acrylamide.

8. The method for preparing the polyacrylic acid powder binder according to any one of claims 4 to 7, characterized in that: The raw material system also includes a protective glue and an initiator; The protective glue includes at least one of polyvinyl alcohol, polyvinyl pyrrolidone, and sodium carboxymethyl cellulose; And / or, the initiator includes at least one of ammonium sulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, hydrogen peroxide, isoascorbic acid, sodium metabisulfite and sodium bisulfite.

9. A negative electrode plate, characterized in that: The invention comprises the polyacrylic acid powder binder according to any one of claims 1 to 3 or the polyacrylic acid powder binder prepared according to the preparation method of the polyacrylic acid powder binder according to any one of claims 4 to 8.

10. A battery, characterized in that: Including the negative electrode sheet according to claim 9.

Citation Information

Cited By

  • Viscosity-adjustable water-soluble silicon-based negative electrode binder as well as preparation method and application thereof

    CN122234739A